Health Services Place Construction Design Based on Android and ISO/TEC 25010 - Edy Susanto; Wahyu Wijaya Widiyanto (LPPM Politeknik Aceh Selatan, 2023)
Health services are places where health efforts are carried out. The study found several problems with health care information, such as the County's official website providing information on only a few major hospitals, not all locations, and if using the Google Maps application, there are still medical service locations that are not registered, so this application can add data that is not registered in the Google Maps application so that people can know more and find medical places easily. The design method used is a prototype and the testing technique used is ISO/TEC 25010. The results of this research are that the Android-based health service location mapping application in the district can display a list of information on hospitals, health centers, main clinics and google maps. Apart from that, the system testing carried out is the conformity aspect in terms of functionality and usability. Based on the functional suitability test, usability results were obtained with results of 81.6%. The conclusion from the test results using ISO/TEC 25010 testing shows that this application can help the community and can be said to be successful